Methodological Approach to Assessment of Transport Infrastructure Development in Megapolitan Capital Cities: Case Study of Moscow - Chaynikova, Liliya; Sorokina, Natalia; Davydova, Olesya; Khristov, Todor; Sedova, Nadezhda (Anais Brasileiros de Estudos Turísticos, 2022)
The objective of the study is to identify and analyze the connection between the trends of the social and economic development of Moscow and the factors of transport infrastructure (TIS) development. The main research methods are the index method and the economic and mathematical modeling. This method helped to specify the infrastructure factors that determine the spatial development of the city and rationalize management decisions aimed at optimizing the development of various types of transport, communications and types of transportation to ensure a sustainable social and economic development of the capital. The author’s approach to calculating the quality of TIS index is presented, which allows, in contrast to similar methodologies, a deeper analysis of the way the environmental factor influences the spatial development of the territory. Using the index, the most general patterns in the development of Moscow’s TIS for the period of 2000 to 2020 were identified. An algorithm for the development of the TIS of a megalopolis is proposed, which suggests the differentiation of management decisions to increase the level of the social and economic state of the territory. The practical value of the method consists in determining the impact of TIS development on the trends of investment and economic growth in the region. It has been ascertained that the development of TIS and the improvement of its quality are currently the main reserves of the economic growth of the regions.